2022
DOI: 10.3390/biom12101522
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Radiolabelling Nanoparticles: SPECT Use (Part 1)

Abstract: The use of nanoparticles (NPs) is rapidly increasing in nuclear medicine for diagnostic and therapeutic purposes. Their wide use is due to their chemical–physical characteristics and possibility to deliver several molecules. NPs can be synthetised by organic and/or inorganic materials and they can have different size, shape, chemical composition, and char. These factors influence their biodistribution, clearance, and targeting ability in vivo. NPs can be designed to encapsulate inside the core or bind to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Since there are no other colloidal particulate matters in the system, it could be concluded that these nanoparticles interact with the different body tissues individually while in circulation. Results showed that PNP and G-PNP have high LE and this is crucial for both diagnostic and therapeutic research, as using fewer NPs in vivo results in less adverse or additional biological effects . Additionally, each biological target’s effectiveness is closely associated with properties like molecule size or charge, its particular activity, lipophilicity, stability, and metabolism of the radiolabeled substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are no other colloidal particulate matters in the system, it could be concluded that these nanoparticles interact with the different body tissues individually while in circulation. Results showed that PNP and G-PNP have high LE and this is crucial for both diagnostic and therapeutic research, as using fewer NPs in vivo results in less adverse or additional biological effects . Additionally, each biological target’s effectiveness is closely associated with properties like molecule size or charge, its particular activity, lipophilicity, stability, and metabolism of the radiolabeled substances.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cancer cell permeability is high in case of glutamine than peptide or antibody as targeting agents for imaging and efficient delivery to target cells. 37,38,54 Prior research has shown that the mononuclear phagocytic system (MPS), which includes Kupffer cells in the liver, red-pulp macrophages in the spleen, and alveolar macrophages in the lungs, showed higher in vivo radioactivity uptake. 29 According to our biodistribution evaluation, the kidney had a greater radioactivity uptake level.…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery systems can be radiolabeled using different techniques such as direct or indirect methods, and encapsulation of radioisotopes. In the direct method, radioisotopes bind to the functional groups on the surface of nanoparticles, while bifunctional chelating agents are required in the indirect technique (Varani et al, 2022). In the present study, liposomes were radiolabeled with 68 Ga using an indirect method, since DTPA‐PE was added to the liposome formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study and the other studies in the literature were taken into consideration while deciding the amount of SA (Karpuz et al, 2023;Manosroi et al, 2002Manosroi et al, , 2004. In addition, liposomes could be directly radiolabeled with 68 Ga by the addition of DTPA-PE at the preparation phase of liposomes (Varani et al, 2022). Although lower amount of DTPA-PE (0.1%-7% mol lipid −1 ) was added to the liposome formulation in the literature, that formulations were radiolabeled with Tc 99m or In 111 unlike this study (Liko et al, 2013;Silindir et al, 2013;Whiteman et al, 2001).…”
mentioning
confidence: 99%
“…Although Copper‐64 is a promising radioisotope for PET imaging mainly due to its suitable half‐life (12.7 h), apart from positron emission (β+, 0.653 MeV [17.8%]) it also emits undesirable beta particles (β − , 0.579 MeV [38.4%]). Radiolabeling of liposomes with 99m Tc for imaging has been reported most widely in the literature (Mushtaq et al, 2021; Varani et al, 2022). This is mainly due to the favorable nuclear decay characteristics of 99m Tc for imaging (140 keV gamma emission and 6 h half‐life), low cost and its easy availability from the Mo‐99/Tc‐99m generators (Duatti, 2021).…”
Section: Introductionmentioning
confidence: 99%